An Audit of the Mental Health Admissions to the Paediatric Assessment Unit (PAU) in the Royal Aberdeen Childrens Hospital (RACH) - Billie-Jo Stephen (BJPsych Open)
Aims: To determine the number of mental health admissions to the Paediatric Assessment Unit in the Royal Aberdeen Childrens Hospital to provide a basis for implementing improvements to our knowledge and staffing so that we can provide a higher quality service for this group of patients.